Reflexiones y aportes de la teoría decolonial y las epistemologías del sur a las pedagogías otras - López Ramírez, Kelly Johana (Lee La LEE, 2023)
Reflexiones y aportes de la teoría decolonial y las epistemologías del sur a las pedagogías otras